The Meaning of Profit in Tota'an Doro Pendalungan Culture: an Ethnographic Study - Akhmad Thoha; Aryo Prakoso (International Journal of Religious and Cultural Studies, 2022)
The purpose of this research is to describe one of Pendalungan culture, Tota'an Doro, as a unique culture that still exists, and to explore the meaning of profit. In Pendalungan Tota'an Doroculture, pigeons are released together by the contestant of the race or the community member, beginning with the release of two pigeons from two regions as the symbol of a bride. This research employed qualitative methods of ethnography approach to elucidate how the culture occurs and exists up to this day. To obtain valid and reliable data, interviews involving the leader of pigeon lovers in Wirolegi and other sub-districts were conducted. Through various stages of data analysis, namely data reduction, data grouping, interpretation, it is found that Tota'an Dorodoes not provide adequate financial gain because the treatment cost is greater than the income earned. However, pigeon lovers gain non-financial benefits by attaining friends and relatives, achieving satisfaction as a participant, getting lottery, and exchanging information related to pigeon. This set of explanations suggests that Pendalungan Tota'an Doro culture focuses more on non-financial gains, specifically kinship and familial communication.